PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING DISERTAI MEDIA GAMBAR TERHADAP KOGNITIF SISWA SMAN 1 KOTO XI TARUSAN - Tika Afriyani (Ta'dib, 2018)
Based on the preliminary studies at SMAN 1 Koto XI Tarusan, it was found that the lack of interest and motivation caused the students less active in the learning process. In addition, the teacher’s teaching model and media were not appropriate, especially within human circulatory system material that made the student learning outcomes still under  the Minimum Completion Criteria (KKM). This study aims at figuring out the effectiveness of Discovery Learning Model Plus Pictures on students’ cognitives at class XI students of SMAN 1 Koto XI Tarusan.This is an experimental research with the population class XI 2017/2018 academic year. The sampling method uses purposive sampling; class XI IPA1 as experimental class, and class XI IPA3 as control class. The instrument used in cognitive assessment is the final test with multuple choices. Based on the results of the study, the cognitive results of the experimental class were 81.05 and the control class was 77.39. From this study, it can be concluded that the application of the Discovery Learning learning model plus images influences the cognitive of class XI students of SMAN 1 Koto XI Tarusan